A global phylogenetic regionalization of vascular plants reveals a deep split between Gondwanan and Laurasian biotas. Issue 3 (26th November 2021) - Carta, Angelino; Peruzzi, Lorenzo; Ramírez‐Barahona, Santiago
Summary: Existing global regionalization schemes for plants consider the compositional affinities among biotas, but these have not explicitly considered phylogenetic information. Here, we present for the first time, a phytogeographical delineation of the global vascular flora based on species‐level evolutionary relationships. We analysed 8737 820 geographical occurrence records for vascular plants together with a time‐calibrated phylogeny including 67 269 species. We constructed a global phylogenetic regionalization by estimating species composition and phylogenetic beta diversity among 200 km × 200 km grid cells across the world. We identified de novo 16 phytogeographical units that are deeply split into two clusters: Laurasian and Gondwanan. Our regionalization broadly matches previous schemes, but also highlights the separation of the Gondwanan biota into an Holotropical cluster and an Australian–Neozealandic–Patagonian cluster. In contrast, no clear split among Laurasian and Gondwanan biotas was retrieved when omitting phylogenetic information. The integration of phylogenetic and geographical information provides new insights into the delineation of phytogeographical areas and their historical relationships, enabling the identification of three large, clearly differentiated biotas, here referred to as kingdoms: Holarctic, Holotropical, and Austral. Our results provide further evidence for delineating transition zones and show a clear latitudinal pattern of increasing evolutionary distinctiveness towards the poles.